(untitled) (International Journal of Engineering and Computer Science, 2017)
Today, the entire device’s in electronics needs to be realized with low power and optimized Area architectures because of power consumption and Area are of main consideration along with other performance parameters. Low power consumption helps to reduce heat dissipation, increases battery life and also reliability. Arithmetic and Logic Unit (ALU) is one of the frequent and the most fundamental component in low power processor design. An Arithmetic logic unit (ALU) is a major component of the central processing unit of a computer system. It does all process related to arithmetic and logic operations that need to be done on instruction words. As the operations become more complex the ALU also become more complex, more expensive and takes up more space in the CPU hence power consumption is a major issue. In this research work the power flow analysis of ALU circuits is analyzed and optimization of ALU power supply unit.